Using stable isotopes to assess whether two sympatric dolphin species share trophic resources - Loizaga de Castro, Rocio; Saporiti, Fabiana; Vales, Damián Gustavo; Cardona, Luis; Crespo, Enrique Alberto (Marine Mammal Science)
In the southwestern South Atlantic Ocean, the dusky dolphin, Lagenorhynchus obscurus, and the short-beaked common dolphin, Delphinus delphis, overlap in their distribution along the Patagonian shelf and beyond the shelf-break from 38°S to 42°S. In coastal waters, these species can be found living in sympatry in the Golfo San Matıas (40°450S and 42°140S), although they differ in their habitat use patterns. In this sense, short-beaked common dolphins prefer habitats located in the northwest section of the gulf far from the coast; whereas dusky dolphins prefer areas with steep slopes close to the coast in the southwestern sector of the gulf. Fil: Loizaga de Castro, Rocio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Saporiti, Fabiana. Universidad de Barcelona; España Fil: Vales, Damián Gustavo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Cardona, Luis. Universidad de Barcelona; España Fil: Crespo, Enrique Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina